Families of particles with different masses in PT-symmetric quantum field theory - Bender, Carl M.; Klevansky, Sandra Pamela (Physical review letters, 2010)
An elementary field-theoretic mechanism is proposed that allows one Lagrangian to describe a family of particles having different masses but otherwise similar physical properties. The mechanism relies on the observation that the Dyson-Schwinger equations derived from a Lagrangian can have many different but equally valid solutions. Nonunique solutions to the Dyson-Schwinger equations arise when the functional integral for the Green’s functions of the quantum field theory converges in different pairs of Stokes’ wedges in complex-field space, and the solutions are physically viable if the pairs of Stokes’ wedges are PT symmetric.